2018
DOI: 10.1051/0004-6361/201731399
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of theSFRMplane atz< 3: single fitting versus multi-Gaussian decomposition

Abstract: The analysis of galaxies on the star formation rate -stellar mass (SFR-M * ) plane is a powerful diagnostic for galaxy evolution at different cosmic times. We consider a sample of 24463 galaxies from the CANDELS/GOODS-S survey to conduct a detailed analysis of the SFR-M * relation at redshifts 0.5 z <3 over more than three dex in stellar mass. To obtain SFR estimates, we utilise mid-and far-IR photometry when available, and rest-UV fluxes for all the other galaxies. We perform our analysis in different redshif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(101 citation statements)
references
References 69 publications
9
90
2
Order By: Relevance
“…, showing that the starburst phenomenon is much more common among intermediate-mass than massive galaxies at z 4 5 -, consistently to what is predicted by theoretical galaxy models (e.g., Cowley et al 2017) and observed at lower redshifts (e.g., Bisigello et al 2017).…”
Section: The Importance Of Starburst Galaxies At Z∼4-5supporting
confidence: 83%
See 3 more Smart Citations
“…, showing that the starburst phenomenon is much more common among intermediate-mass than massive galaxies at z 4 5 -, consistently to what is predicted by theoretical galaxy models (e.g., Cowley et al 2017) and observed at lower redshifts (e.g., Bisigello et al 2017).…”
Section: The Importance Of Starburst Galaxies At Z∼4-5supporting
confidence: 83%
“…Here we show, for the first time, that starburst galaxies make a clearly distinct sequence on the SFR-M * plane and constitute a significant percentage ( 15% ) of all galaxies with M 9.2 log 10.8 10 *   at z 3.9 4.9   . Only a slightly smaller percentage is obtained at z 2 3 -when a broad dynamic range in stellar mass is considered, albeit with significantly lower sSFR (Bisigello et al 2017). We find that the fraction of starburst galaxies has a strong dependence on stellar mass, varying from ∼0.25 at M log 9.3 10 *( ) to 0.05…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…All SMGs here have redshift information and a single component at ∼0 2 resolution. More than 15 out of the 25 are located above 4´the main sequence at z 2 in the stellar mass versus SFR plane (Figure 2), indicating that the majority of the sample are starbursts (Bisigello et al 2017). Note that among the 29 SMGs with z=1-3, four are not used in the analysis: two SMGs are not detected at 24 μm and the other are blended in the IRAC maps.…”
Section: Relation Between Millimeter Sizes and Agnmentioning
confidence: 99%